EFFECT OF COMBINATION WARM WATER FOOT SOAK THERAPY AND LEMON AROMATHERAPY ON BLOOD PRESSURE IN ELDERLY WITH HYPERTENSION: CASE REPORT - Teguh Triana; Galih Noor Alivian; Lita Heni Kusumawardani (International Journal of Biomedical Nursing Review, 2025)
Introduction: Hypertension is a condition where blood pressure increases abnormally on several examinations with systolic and diastolic blood pressure measurements ≥140/90 mmHg. The elderly are vulnerable to hypertension because old age is a phase where the body has experienced physiological decline so that it is more susceptible to disease. Hypertension can be treated pharmacologically and non-pharmacologically. Non-pharmacological therapy that can be given to patients with hypertension is a combination of warm water foot soak therapy and aromatherapy lemon. Purpose: This case study aims to determine the effect of a combination of warm water foot soak therapy and lemon aromatherapy on elderly people with hypertension. Methods: The method used in this research is a case study with 3 hypertensive elderly subjects. The focus of this study is the application of evidence-based practice in the form of a combination of warm water foot soak therapy and lemon aromatherapy for 3 consecutive days for 15 minutes. Discussion: The results of the study showed that warm water foot soak therapy and lemon aromatherapy could reduce blood pressure in elderly people with hypertension with an average decrease in systolic and diastolic blood pressure for the three clients, namely 15.1 mmHg and 8.5 mmHg. Conclusion: Warm water foot soak therapy and lemon aromatherapy have an effect on lowering blood pressure in elderly people with hypertension.